Electrophoretic Studies on Eye Lens and Muscle Proteins of some Flat Fishes off Bombay Coast - Apte, Deepak; Rao, Maithili (Fishery Technology, 2025)
Electrophoretic profiles of eye lens protein and muscle proteins of Cynoglossus macroIepidotus, Pseudorhombus elevatus, ZebriasÂ quagga and Asopia cornuta show species specific band pattern. A total of 8, 9, 10 and 9 bands in eye lens proteins and 7, 5, 9 and 5 bands in muscle proteins were observed in the above mentioned fishes respectively. The use of electrophoretic profile of eye lens proteins and muscle proteins in fish taxonomy is discussed.